2002
DOI: 10.1093/gerona/57.7.m422
|View full text |Cite
|
Sign up to set email alerts
|

The Eden Alternative: Findings After 1 Year of Implementation

Abstract: The findings from this study indicate no beneficial effects of the EA in terms of cognition, functional status, survival, infection rate, or cost of care after 1 year. However, qualitative observations at the Eden site indicated that the change was positive for many staff as well as residents, suggesting that it may take longer than a year to demonstrate improvements attributable to the EA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
68
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 4 publications
1
68
1
Order By: Relevance
“…Overall medication use was examined in 2 studies in Eden Alternative settings and 2 in nondementia-specific small houses. 18,27,44,45 None of the studies reported significant differences in overall medication use compared with traditional NH settings. One Eden Alternative study 44 and one nondementia-specific small house study 45 found no differences in the prevalence of pressure ulcers compared with traditional NH settings.…”
Section: Physical Outcomesmentioning
confidence: 97%
See 4 more Smart Citations
“…Overall medication use was examined in 2 studies in Eden Alternative settings and 2 in nondementia-specific small houses. 18,27,44,45 None of the studies reported significant differences in overall medication use compared with traditional NH settings. One Eden Alternative study 44 and one nondementia-specific small house study 45 found no differences in the prevalence of pressure ulcers compared with traditional NH settings.…”
Section: Physical Outcomesmentioning
confidence: 97%
“…Three of the 5 studies focusing on Eden Alternative settings examined a physical functioning outcome and found no significant effects compared with traditional NH settings. 18,43,44 One of 2 studies in nondementia-specific small houses reported that residents in the small, homelike settings had or maintained functioning better than those in traditional NHs. 27 Kane et al 45 reported mixed findings with no significant differences in selfreported ADLs or instrumental ADLs among residents in the homelike compared with 2 traditional NHs, whereas based on Minimum Data Set quality indicators, residents in the homelike setting had less decline in the late loss of ADLs than residents in the comparison NHs.…”
Section: Physical Outcomesmentioning
confidence: 99%
See 3 more Smart Citations